2022
DOI: 10.1038/s41467-022-34665-z
|View full text |Cite
|
Sign up to set email alerts
|

Stromal FOXF2 suppresses prostate cancer progression and metastasis by enhancing antitumor immunity

Abstract: Cancer-associated fibroblasts (CAFs) mediate an immunosuppressive effect, but the underlying mechanism remains incompletely defined. Here we show that increasing prostatic stromal Foxf2 suppresses the growth and progression of both syngeneic and autochthonous mouse prostate cancer models in an immunocompetent context. Mechanistically, Foxf2 moderately attenuates the CAF phenotype and transcriptionally downregulates Cxcl5, which diminish the immunosuppressive myeloid cells and enhance T cell cytotoxicity. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Again, FOXF2 (Forkhead Box F2) in the prostate stroma reduced the iCAF phenotypic ratio, induced its transformation to myCAF, and downregulated CXCL5, thereby reducing immunosuppressive myeloid cells and enhancing T cell cytotoxicity. Further, increasing the content of Foxf2 sensitized PCa to ICB therapy [ 413 ]. The gene set variation analysis by Zhai, X., and colleagues indicated that pathways like PPAR, GnRH, and mTOR are significantly correlated with PCa and might become targeted landmarks [ 414 ].…”
Section: Background Knowledge Of Cafsmentioning
confidence: 99%
“…Again, FOXF2 (Forkhead Box F2) in the prostate stroma reduced the iCAF phenotypic ratio, induced its transformation to myCAF, and downregulated CXCL5, thereby reducing immunosuppressive myeloid cells and enhancing T cell cytotoxicity. Further, increasing the content of Foxf2 sensitized PCa to ICB therapy [ 413 ]. The gene set variation analysis by Zhai, X., and colleagues indicated that pathways like PPAR, GnRH, and mTOR are significantly correlated with PCa and might become targeted landmarks [ 414 ].…”
Section: Background Knowledge Of Cafsmentioning
confidence: 99%
“…CAFs, as a crucial component of the tumor microenvironment, plays a critical role in PCa progression [25]. [27]. In our current study, we uncovered that the hypoxic TME stimulates CAFs to release exosomes rich in miR-500a-3p, which subsequently in uence PCa phenotypes by targeting speci c mRNA.…”
Section: Discussionmentioning
confidence: 59%
“…In prostate cancer, HIC2 protein expression was shown to be increased in tumors compared with benign hyperplasia and normal tissue with a Gleason score greater than 7 and grade 3 ( 52 ). Collagen Type III Alpha 1 Chain (COL3A1) is a protein that is found in most soft connective tissues along with type I collagen ( 53, 54 ). It is involved in the regulation of cortical development, and it is the major ligand of ADGRG1 in the developing brain.…”
Section: Resultsmentioning
confidence: 99%